Correction: Regulation of aggregation-induced emission behaviours and mechanofluorochromism of tetraphenylethene through different oxidation states of sulphur moieties. Issue 44 (1st November 2019) - Yang, Qin; Li, Dongyang; Chi, Weijie; Guo, Ronghui; Yan, Bin; Lan, Jianwu; Liu, Xiaogang; Yin, Jun
Abstract : Correction for 'Regulation of aggregation-induced emission behaviours and mechanofluorochromism of tetraphenylethene through different oxidation states of sulphur moieties' by Qin Yang et al., J. Mater. Chem. C, 2019, 7, 8244–8249.